Stability of Genetic and Environmental Effects from Adolescence to Young Adulthood: Results of Croatian Longitudinal Twin Study of Personality - Bratko, Denis (Array, 2007)
The primary aim of this study was to conduct a bivariate genetic analysis investigating the extent to which genetic and environmental factors contribute to stability and change in personality factors in the period from adolescence to young adulthood on a sample of Croatian twins. The sample used in this research was formed in 1992 based on a register of citizens of Zagreb and data was collected for 160 twin pairs (75 monozygotic and 85 dizygotic twin pairs). Twins were tested twice, 4 years apart with the Eysenck Personality Questionnaire (mean age at first time point was 17 years). Univariate analyses indicate that the best fitting model for extraversion, neuroticism, psychoticism and lie scale at both time points includes additive genetic (A) and nonshared environmental (E) influences, with heritability stimates in the .40 to .50 range. Longitudinal analyses using AE correlated factors model ndicate that genetic factors contribute mainly to tability, while environmental factors contribute mainly to change in personality during that 4-year period of transition from adolescence to young adulthood.